2022
DOI: 10.1037/prj0000485
|View full text |Cite
|
Sign up to set email alerts
|

Family social networks and personal recovery among Chinese people with mental illness in Hong Kong: The mediating effects of self-esteem and self-efficacy.

Abstract: Objective: This study investigated the mediating roles of self-esteem and self-efficacy on the relationship between family social networks and personal recovery among Chinese people with mental illness in Hong Kong. Methods: One hundred and twenty-five Chinese adults with mental illness from community mental health centers in Hong Kong were recruited for this study. Data were collected using a structured questionnaire. Results: Study results indicated that a large family network size was indirectly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was found that self‐efficacy significantly mediated the pathway of ICT use for social interactions, leisure and entertainment, information and consultation and learning and skill upgrading on academic achievement and mental health. As a dispositional factor, self‐efficacy can effectively motivate students to improve academic achievement and develop a high level of mental health through ICT use (Zhou et al, 2020; Chang & Chen, 2022). Also, the mediating role of technostress was confirmed in the pathways of ICT use for social interactions, leisure and entertainment, and learning and skill upgrading on academic achievement and mental health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that self‐efficacy significantly mediated the pathway of ICT use for social interactions, leisure and entertainment, information and consultation and learning and skill upgrading on academic achievement and mental health. As a dispositional factor, self‐efficacy can effectively motivate students to improve academic achievement and develop a high level of mental health through ICT use (Zhou et al, 2020; Chang & Chen, 2022). Also, the mediating role of technostress was confirmed in the pathways of ICT use for social interactions, leisure and entertainment, and learning and skill upgrading on academic achievement and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the direct influence, the indirect influence of self‐efficacy, as a representative psychological factor, on the relationship between ICT use and education development has also attracted attention (Alghamdi et al, 2020; Kim et al, 2020). Specifically, research has found that self‐efficacy significantly mediates the relationship between ICT use and academic achievement and mental health (Zhou et al, 2020; Chang & Chen, 2022). Combined with the O‐P framework, considering the prominent promoting role of self‐efficacy in motivating students to participate in learning and affecting students' psychological state (Zhou & Yu, 2021), the study included self‐efficacy as a propensity factor in the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rodebaugh and Goldin et al showed that in socially anxious individuals, lower self-efficacy predicts poorer behavioral performance of speech tasks and interactions with others [40,41]. However, high self-efficacy is related, for example, to the regulation of stress, higher self-esteem, better well-being, good physical conditioning, and adaptation to and recovery from acute and chronic diseases [42,43]. Moreover, a high sense of self-efficacy is associated with positive feelings about one's self, which facilitate cognitive processes, academic achievements, confidence, and motivation [44].…”
Section: Social Cognitive Theory and Self-efficacymentioning
confidence: 99%